2007
DOI: 10.1124/mol.107.039644
|View full text |Cite
|
Sign up to set email alerts
|

Cystine-Glutamate Transporter SLC7A11 Mediates Resistance to Geldanamycin but Not to 17-(Allylamino)-17-demethoxygeldanamycin

Abstract: The cystine-glutamate transporter SLC7A11 has been implicated in chemoresistance, by supplying cystine to the cell for glutathione maintenance. In the NCI-60 cell panel, SLC7A11 expression shows negative correlation with growth inhibitory potency of geldanamycin but not with its analog 17-(allylamino)-17-demethoxygeldanamycin (17

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…The SLC7A11 and SLC3A2 genes, encoding the heterodimeric amino acid transporter x À c , have been implicated in chemoresistance, by supplying cystine to the cell for glutathione synthesis (28). We experimentally confirmed that the x À c transporter confers resistance selectively to GA analogues with methoxy group or unsubstituted at C17 position, but not to analogues with amino group at the C17 position (29). Thus, using pharmacogenomics approach we have identified that, multiple transporters, either directly (by substrate-transporter interaction) or indirectly (by increasing glutathione levels), may contribute to tumors' sensitivity and resistance to GA analogues.…”
Section: Discussionsupporting
confidence: 66%
“…The SLC7A11 and SLC3A2 genes, encoding the heterodimeric amino acid transporter x À c , have been implicated in chemoresistance, by supplying cystine to the cell for glutathione synthesis (28). We experimentally confirmed that the x À c transporter confers resistance selectively to GA analogues with methoxy group or unsubstituted at C17 position, but not to analogues with amino group at the C17 position (29). Thus, using pharmacogenomics approach we have identified that, multiple transporters, either directly (by substrate-transporter interaction) or indirectly (by increasing glutathione levels), may contribute to tumors' sensitivity and resistance to GA analogues.…”
Section: Discussionsupporting
confidence: 66%
“…10). In support of this idea, system x c -inhibitors can lead to intracellular GSH depletion and reverse the multidrug resistance of cells to certain anticancer drugs in vitro (45,93,150,206). In another study, it was demonstrated that system x c -specifically mediates resistance to anticancer drugs that produce high amounts of ROS, such as geldanamycin and celastrol (150,206).…”
Section: System X C 2 In Health and Diseasementioning
confidence: 77%
“…The cystine/glutamate exchanger x c -is involved in the transport of cystine, and is a key regulator of cellular GSH levels mediating chemoresistance to cytotoxic agents [16,37] . Inhibition of the cystine transporter with the aim of depleting GSH has been suggested as a therapeutic potential in treatment of human lymphomas and leukemias [14,38,39] , breast cancers [12,40] and gliomas [41,42] .…”
Section: Discussionmentioning
confidence: 99%